Penanaman Dalugha Secara Berintegrasi Dengan Mangrove di Bahowo Mangrove Park bermitrakan Kelompok Tani Tunas Baru Bahowo - Dino Rahardiyan; Mario V. Poluakan; Jantje Ngangi (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The village of Bahowo-Lingkungan IV – Tongkaina District - Bunaken, is the farthest Northern shoreline of Manado, considered as the ecological buffer area for Bunaken National Marine Conservation Park and the rest of Manado shoreline areas, due to its 6 hectares of pristine ecological mangrove forest. Therefore, Manado City Government has declared Bahowo as the last line of defence towards Manado's overpowering industrialization and shoreline reclamation programs that has cut down most of Manado's mangrove habitat. The Bahowo area before COVID-19 was also previously programmed to be an Ecotourism area, supporting the marine ecosystems of the Bunaken Marine Conservation Park. Geographic Research Letter 2019 and UNEP Report 2026 has had the world preparing for global warming, North Sulawesi included. A previous research exploring for potential future staple food resulted an endemic underutilized plant of the Sangihe-Talaud islands, the Cyrtosperma Merkusii (Dalugha to the locals). A potential food plant tolerant to brackish habits (0.59-1.91ppt salinity). Bahowo and their Tunas Baru Farmer Group was chosen to disseminate these research results to integrate Dalugha with mangroves in 3 activities; A dissemination of the Dalugha plant in Biological-Ecological-Cultivation Aspects, Organic Fertilizer Coaching Clinic, and Dalugha Corm Processing Coaching Clinic.